Tingkat Penggunaan Gadget (Smartphone) dan Prestasi Belajar Siswa - Anita Amelia Ole; Lilis Kodina (Journal on Education, 2023)
The development of the era is also followed by technological developments in terms of communication, this can be seen by the increasing sophistication of smartphones, causing students to be more interested in these sophisticated objects than having to study to achieve learning achievements at school. The purpose of this study is to see the level of use of smartphone gadgets and student achievement. Haomasan and Nofharina (2018) mean that teenagers' use of smartphone gadgets varies, some are due to the sophistication of their features, being able to access the internet quickly, easily accessing social media, as a means of entertainment, and helping to complete school assignments. This research uses quantitative research. The results of this conclusion indicate that the use of smartphone gadgets is placed in the frequent category with the sum of the average or mean values ​​(M) = 3.97. and the results of student achievement in science subjects are in the very good category. The advice from this study is to maintain the level of student achievement, but don't forget to control the time when using smartphone gadgets because it will hurt student achievement if you use smartphone gadgets too often.